Catalyst for preparing formic acid by reducing carbon dioxide with low energy consumption and high selectivity in wide current density range as well as preparation method and application of catalyst

By using an ordered intermetallic alloy catalyst in the CO2 reduction catalyst, the low efficiency problem of CO2 reduction to formic acid at wide current density is solved, and electrochemical catalysis with high selectivity and low energy consumption is achieved, which is suitable for industrial applications.

CN119221019AActive Publication Date: 2024-12-31XIAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411425386.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Within a wide current density range, it is difficult for the prior art to achieve an electrochemical catalytic process of reducing CO2 to formic acid with low energy consumption and high selectivity, especially due to the chemical inertia of CO2 and the complex reaction mechanisms, which lead to high electrical energy input and low selectivity.

Method used

Using an intermetal alloy catalyst, the surface atoms are arranged in a highly ordered periodic manner. Through the alloying process of preparing palladium templates and inorganic bismuth salts, a catalyst with a continuous adjustable metal ratio is formed, and an ultrasonic etching and reduction atmosphere is used. Carry out reactions to optimize the structure and performance of the catalyst.

Benefits of technology

Within a wide current density range of 100-400 mA cm-2, the catalyst exhibits a Faraday efficiency of 95% formic acid and a 57.5% energy efficiency, significantly reducing voltage and energy consumption requirements, making it suitable for large-scale production and applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221019A_ABST
    Figure CN119221019A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst for preparing formic acid through low-energy-consumption and high-selectivity reduction of carbon dioxide within a wide current density range and a preparation method and application thereof.The preparation method of the catalyst comprises the steps that S1, a palladium template is prepared, specifically, sodium chloropalladate, porous silicon and water are mixed, a reducing agent solution is added after vacuum drying is conducted, centrifugation, washing and secondary vacuum drying are conducted, and the palladium template is obtained; a palladium template is obtained; s2, alloying: mixing an inorganic bismuth salt and a palladium template, and calcining in a reducing atmosphere; and S3, etching: putting the reduction reaction product obtained in the step S2 into alkali liquor in ultrasound to etch the porous silicon, and washing. The size of the catalyst is uniform, the diameter is 118 + / -0.4 nm, the bismuth-palladium metal ratio is adjustable in a wide range, the product metal ratio and the feeding metal ratio have a good linear relationship, the surface atom arrangement shows highly-ordered light and dark atom alternating periodic arrangement, and the catalyst has a good application prospect. And the catalyst shows excellent catalytic selectivity and energy efficiency on formic acid prepared by electrochemical reduction of carbon dioxide in a wide current density range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanocatalysts, and in particular to a catalyst for producing formic acid with low energy consumption and high selectivity by reducing carbon dioxide in a wide current density range, and a preparation method and application thereof. Background Art

[0002] Among various CO2 conversion methods, using green electricity to electrochemically reduce CO2 to value-added chemicals is considered to be an effective way to achieve carbon recycling and renewable energy storage at the same time. Among the many products of CO2 electrochemical reduction reaction, formic acid is the product with the most commercial value. In addition, formic acid can not only be used as a fuel for direct formic acid fuel cells, but also as a liquid hydrogen storage carrier to solve the storage and transportation problems of hydrogen energy and build a sustainable hydrogen storage system for the goal of "carbon neutrality".

[0003] Linear molecule CO2 is chemically inert and has low electron affinity. There is a large energy gap (13.7 eV) between its lowest unoccupied molecular orbital and its highest occupied molecular orbital. Therefore, the electrochemical conversion process of CO2 often requires a large amount of electrical energy input. In addition, the CO2 electroreduction reaction process is complex, with up to 16 reaction products. Therefore, the CO2 electroreduction process for preparing formic acid still has the problem of low selectivity. At the same time, the current density in the electrochemical CO2 reduction process directly affects its future industrialization cost. At present, it is still a huge challenge to achieve low energy consumption and high selectivity to reduce CO2 to formic acid in a wide and large current density range.

[0004] At present, the catalysts for electrochemical CO2 reduction to formic acid are usually p-block metals (Sn, Bi, etc.), which are poor catalysts for the hydrogen evolution reaction. However, due to their weak adsorption energy, the CO2 reduction process on the surface of such catalysts exhibits a high overpotential. In contrast, palladium is the only known metal that is expected to achieve CO2 reduction to formic acid at near zero overpotential. However, CO poisoning and competition with the hydrogen evolution reaction limit the application of palladium-based catalysts in CO2 conversion. Summary of the invention

[0005] The technical problem to be solved by the present invention is the challenge mentioned in the background technology, and provides an intermetallic alloy catalyst for reducing CO2 to formic acid with low energy consumption and high selectivity in a wide current density range. The surface atoms of the catalyst are highly ordered and periodically arranged, and have a continuously adjustable metal ratio. Compared with single metal and alloy catalysts with disordered surface atoms, it exhibits lower electrical energy demand and higher formic acid selectivity in a wider current density range.

[0006] In order to solve the above problems, the present invention proposes the following technical solutions: In a first aspect, the present invention provides a method for preparing an intermetallic alloy catalyst for reducing CO2 to formic acid with low energy consumption and high selectivity in a wide current density range, comprising the following steps: S1. Preparation of palladium template: mixing chloropalladate, porous silicon and water, vacuum drying and adding a reducing agent solution to carry out a reduction reaction, centrifuging, washing, and vacuum drying for a second time to obtain a palladium template; S2 alloying: mixing an inorganic bismuth salt and the palladium template, and calcining in a reducing atmosphere to perform a reduction reaction; S3. Etching: placing the reduction reaction product obtained in step S2 in an alkaline solution under ultrasound to etch the porous silicon, and washing it to obtain the ordered metal catalyst for catalyzing carbon dioxide to produce formic acid.

[0007] Optionally, in step S1, the reducing agent is selected from at least one of ascorbate, glucose and sodium borohydride.

[0008] Optionally, in step S1, the mass ratio of chloropalladate to porous silicon is 0.05-0.06:0.1-0.3.

[0009] Optionally, in step S1, the molar ratio of the chloropalladate to the reducing agent is 0.15-0.2:1-3.

[0010] Optionally, in step S2, the inorganic bismuth salt is bismuth chloride.

[0011] In the present application, the molar ratio of the inorganic bismuth salt to the chloropalladium salt is 0.3-5:1.

[0012] Optionally, in step S2, the reducing atmosphere is selected from a hydrogen / argon mixed gas.

[0013] Optionally, in the hydrogen / argon mixed gas, the volume ratio of hydrogen to argon is 5-9:95-5.

[0014] Optionally, in step S2, the calcination temperature is 280-320° C., and the calcination time is 5-7 h.

[0015] Optionally, in step S3, the concentration of the alkali solution is 1-3 mol / L.

[0016] Optionally, in step S3, the alkali solution may be selected from sodium hydroxide solution, potassium hydroxide solution or a combination thereof.

[0017] Optionally, in step S3, the etching time is 10-20 min.

[0018] In a second aspect, the present application also provides a catalyst prepared according to the method described above.

[0019] In a third aspect, the present application also provides the use of the catalyst prepared according to the method as described above in catalytic carbon dioxide oxidation to produce formic acid.

[0020] Beneficial effects of the present invention: The preparation method of the invention has simple process, good reproducibility, is suitable for large-scale production, and can meet large-scale use.

[0021] The ordered intermetallic catalyst of the present invention has uniform size and a diameter of 118 ± 0.4 nm. The bismuth-palladium metal ratio is adjustable in a wide range and there is a good linear relationship between the product metal ratio and the feed metal ratio. The surface atomic arrangement shows a highly ordered periodic arrangement of alternating light and dark atoms.

[0022] The ordered intermetallic catalyst of the present invention exhibits excellent catalytic selectivity for the electrochemical reduction of carbon dioxide to formic acid in a wide current density range, and the electrochemical selectivity is 100-400 mA cm -2 Within this range, the Faraday efficiency of formic acid remains at around 95%.

[0023] The ordered intermetallic catalyst of the present invention exhibits significantly reduced voltage requirements and excellent energy efficiency for the electrochemical reduction of carbon dioxide to formic acid over a wide current density range, with a current density of 100 mA cm -2 When the reaction temperature is 200 ℃ and the total cell voltage is only 2.37 V, the energy efficiency of formic acid product is as high as 57.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 . A relationship diagram between the actual atomic ratio and the synthetic feed ratio of the palladium-bismuth intermetallic alloy catalyst prepared in Examples 1-6 of the present invention.

[0025] Figure 2 . TEM image of the palladium-bismuth intermetallic alloy catalyst prepared in Example 4 of the present invention.

[0026] Figure 3 . HAADF-STEM image of the palladium-bismuth intermetallic alloy catalyst prepared in Example 4 of the present invention.

[0027] Figure 4 . Activity diagram of electrochemical reduction of carbon dioxide catalyzed by the palladium-bismuth intermetallic alloy catalyst prepared in Example 4 of the present invention.

[0028] Figure 5 . HRTEM image of the palladium-bismuth alloy catalyst prepared in Example 7 of the present invention.

[0029] Figure 6 . This is a comparison chart of the activities of the catalysts prepared in Examples 4 and 7 of the present invention.

[0030] Figure 7. A comparison chart of the full cell voltages of the catalysts prepared in Examples 4 and 7 of the present invention.

[0031] Figure 8 . A comparison chart of the energy efficiencies of the catalysts prepared in Examples 4 and 7 of the present invention. DETAILED DESCRIPTION

[0032] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.

[0033] It should be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present invention, and thus the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0034] In the following description, numerous details are discussed to provide a more thorough explanation of embodiments of the present invention; however, it is apparent to one skilled in the art that embodiments of the present invention may be practiced without these specific details. Example 1

[0035] S1. 53.3 mg of sodium chloropalladate and 0.2 g of KIT-6 porous silicon were added to 2 mL of water, vacuum dried at 60 °C for 6 h, and then 2 mL of 1 mol / L ascorbic acid aqueous solution was added. After standing at room temperature for 12 h, the mixture was centrifuged. The precipitate obtained by centrifugation was washed with water three times and vacuum dried at 60 °C to obtain a palladium template. S2. The palladium template obtained in step S1 was ground and mixed with 19 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300 ° C for 6 h; S3. The calcined product was placed in 10 mL of 2 mol / L sodium hydroxide aqueous solution, ultrasonicated for 15 min and then centrifuged, repeated 5 times, replaced the sodium hydroxide solution with water, repeated the above washing steps, and then vacuum dried at 60 °C to obtain an intermetallic catalyst for catalyzing carbon dioxide to formic acid.

[0036] The bismuth-palladium metal atomic ratio (ie, the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example was detected by energy dispersive x-ray spectroscopy.

[0037] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown. Example 2

[0038] The difference between this embodiment and embodiment 1 is that: S2. The palladium template obtained in step S1 was ground and mixed with 57.1 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300° C. for 6 h.

[0039] The bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example is detected by the same detection method as in Example 1.

[0040] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown. Example 3

[0041] The difference between this embodiment and embodiment 1 is that: S2. The palladium template obtained in step S1 was ground and mixed with 114.2 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300° C. for 6 h.

[0042] The bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example is detected by the same detection method as in Example 1.

[0043] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown. Example 4

[0044] The difference between this embodiment and embodiment 1 is that: S2. The palladium template obtained in step S1 was ground and mixed with 171.4 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300° C. for 6 h.

[0045] The bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example is detected by the same detection method as in Example 1.

[0046] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown.

[0047] The TEM image of the palladium-bismuth intermetallic alloy catalyst prepared in the embodiment of the present invention is shown in Figure 2 , HADDF-STEM image see Figure 3 .

[0048] Depend on Figure 2 and Figure 3 It can be seen that the palladium-bismuth intermetallic alloy catalyst prepared in Example 4 of the present invention has a uniform size (118 ± 0.4 nm) and the surface atoms show a highly ordered periodic arrangement of alternating light and dark atoms.

[0049] The prepared palladium-bismuth alloy catalyst was used to carry out the electrochemical reduction of carbon dioxide to prepare formic acid test. The specific steps are as follows: 10 mg of the palladium-bismuth intermetallic alloy catalyst prepared in the embodiment of the present invention and 1 mg of XC-72 carbon were weighed and added to 1 mL of a 1:1 ethanol / water mixture, and then 30 μL of naphthol solution was added. After ultrasonic treatment for 15 minutes, the mixture was evenly sprayed onto the surface of carbon paper (1.25 cm × 1.25 cm) and dried under an infrared lamp. The catalyst was tested for carbon dioxide reduction using a membrane electrode electrolytic cell, with 1 M KOH as the anode electrolyte and a flow rate of 2 mL / min at the anode. The anode used a titanium mesh (2 cm × 2 cm) coated with iridium dioxide, and the cathode used a CO2 gas with a flow rate of 50 sccm (corrected by the tail gas flow rate).

[0050] The reaction process adopted constant current mode, set different current densities, recorded the voltage corresponding to each current density, and began to collect gas phase products at 600 s. The gas content was determined by gas chromatography, and the liquid phase products were tested by nuclear magnetic resonance.

[0051] The Faraday efficiency of formic acid production of the palladium-bismuth intermetallic alloy catalyst prepared in the embodiment of the present invention at various current densities is shown in Figure 4 .

[0052] Depend on Figure 4 It can be seen that in the range of 100 ~ 400 mA cm -2 In a wide current density range, the formic acid Faraday efficiency of the intermetallic catalyst prepared in Example 4 for catalyzing carbon dioxide to produce formic acid is maintained at about 95%.

[0053] The palladium-bismuth intermetallic alloy catalyst prepared in the embodiment of the present invention has a high conductivity at 200 mA cm -2 The current density corresponds to the battery voltage. Figure 7 , formic acid production energy efficiency see Figure 8 . Example 5

[0054] The difference between this embodiment and embodiment 1 is that: S2. The palladium template obtained in step S1 was ground and mixed with 228.5 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300° C. for 6 h.

[0055] The bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example is detected by the same detection method as in Example 1.

[0056] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown. Example 6

[0057] The difference between this embodiment and embodiment 1 is that: S2. The palladium template obtained in step S1 was ground and mixed with 285.6 mg of bismuth chloride, and then placed in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95, and calcined at 300° C. for 6 h.

[0058] The bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this example is detected by the same detection method as in Example 1.

[0059] The relationship between the bismuth-palladium metal atomic ratio (i.e., the actual bismuth-palladium metal atomic ratio) of the intermetallic catalyst for catalyzing carbon dioxide to produce formic acid prepared in this embodiment and the synthetic feed ratio is as follows: Figure 1 shown. Example 7

[0060] 53.3 mg of sodium chloropalladate and 150 mg of XC-72 carbon were added to 2 mL of water and vacuum dried at 60 °C for 6 h. Subsequently, 2 mL of 1 M (mol / L) ascorbic acid aqueous solution was added. After standing at room temperature for 12 h, the mixture was centrifuged, washed with water three times, and vacuum dried at 60 °C to obtain a palladium template.

[0061] The obtained palladium template was thoroughly ground and mixed with 171.4 mg of bismuth chloride, and then calcined at 300°C for 6 h in a hydrogen / argon mixed atmosphere with a volume ratio of 5:95 to obtain an intermetallic alloy catalyst, the HRTEM image of which is shown in Figure 5 .

[0062] Depend on Figure 5 It can be seen that the atomic arrangement on the surface of the palladium-bismuth alloy catalyst prepared in Example 7 is not periodic.

[0063] The prepared palladium-bismuth alloy catalyst was used to carry out the electrochemical reduction of carbon dioxide to prepare formic acid test. The specific steps are as follows: Weigh 20 mg of the palladium-bismuth alloy catalyst prepared in the embodiment of the present invention and add it to 1 mL of ethanol / water mixture with a volume ratio of 1:1, then add 30 μL of naphthol solution, and after ultrasonic treatment for 15 minutes, spray it evenly on the surface of carbon paper (1.25 cm × 1.25 cm), and dry it under an infrared lamp; use a membrane electrode electrolytic cell to test the catalyst for carbon dioxide reduction, use 1 M KOH solution as the anode electrolyte, and the anode flow rate is 2 mL / min. The anode uses a titanium mesh (2 cm × 2 cm) coated with iridium dioxide, and the cathode uses CO2 gas with a flow rate of 50 sccm (corrected by the tail gas flow rate).

[0064] The reaction process was carried out in constant current mode. Different current densities were set and the voltage corresponding to each current density was recorded. The gas phase products were collected at 600 s and the gas content was determined by gas chromatography. The liquid phase products were tested by nuclear magnetic resonance at 200 mA cm -2 The Faradaic efficiency of formic acid production at the current density is given by Figure 6 , corresponding to the battery voltage see Figure 7 , formic acid production energy efficiency see Figure 8 .

[0065] The relationship between the atomic ratio of the bismuth-palladium precursor during the preparation of Examples 1-6 of the present invention and the actual atomic ratio of the palladium-bismuth intermetallic alloy catalyst obtained is shown in Figure 1 .

[0066] Depend on Figure 1 It can be seen that there is a good linear relationship between the atomic ratio of the feed and the atomic ratio of the actual sample.

[0067] The ordered palladium-bismuth intermetallic alloy catalyst and the disordered palladium-bismuth alloy catalyst prepared in Examples 4 and 7 of the present invention were subjected to the electrochemical reduction test of carbon dioxide. The current density of the test was 200 mA cm -2 At this current density, the activity comparison results of the catalysts of different embodiments are as follows: Figure 6 shown.

[0068] Depend on Figure 6It can be seen that compared with the palladium-bismuth alloy catalyst with disordered surface structure obtained in Example 7, the palladium-bismuth intermetallic alloy catalyst with highly ordered surface atoms prepared in Example 4 has significantly improved formic acid selectivity.

[0069] The ordered palladium-bismuth intermetallic alloy catalyst and the disordered palladium-bismuth alloy catalyst prepared in Examples 4 and 7 of the present invention were subjected to the electrochemical reduction test of carbon dioxide. The current density of the test was 200 mA cm -2 At this current density, the cell voltage comparison results of the catalysts of different embodiments are as follows: Figure 7 The energy efficiency comparison results are shown in Figure 8 shown.

[0070] Depend on Figure 7 and Figure 8 It can be seen that compared with the palladium-bismuth alloy catalyst with disordered surface structure in Example 7, the palladium-bismuth intermetallic alloy catalyst with highly ordered surface atoms prepared in Example 4 shows smaller energy consumption requirements and higher energy efficiency.

[0071] In summary, the present invention provides an intermetallic alloy catalyst and a preparation method thereof for reducing CO2 to formic acid with low energy consumption and high selectivity within a wide current density range. The arrangement of surface atoms is regulated by the nano-confinement effect of the template, and the highly ordered periodic atomic arrangement optimizes the selectivity of formic acid products within a wide current density range, thereby reducing the electrical energy consumption required for the entire battery.

[0072] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing an ordered intermetallic catalyst for reducing carbon dioxide to formic acid with low energy consumption and high selectivity in a wide current density range, characterized in that: The following steps are involved: S1. Preparation of palladium template: mixing sodium chloropalladate, porous silicon and water, vacuum drying, adding a reducing agent solution to carry out a reduction reaction, centrifuging, washing, and vacuum drying for a second time to obtain a palladium template; S2 alloying: mixing an inorganic bismuth salt and the palladium template, and calcining in a reducing atmosphere to perform a reduction reaction; S3. Etching: placing the reduction reaction product obtained in step S2 in an alkaline solution under ultrasound to etch the porous silicon, and washing it to obtain the ordered metal catalyst for catalyzing carbon dioxide to produce formic acid.

2. The preparation method according to claim 1, characterized in that In step S1, the reducing agent is selected from at least one of ascorbic acid, glucose and sodium borohydride.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of sodium chloropalladate to porous silicon is 0.05-0.06:0.1-0.

3.

4. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of the sodium chloropalladate to the reducing agent is 0.15-0.2:1-3.

5. The preparation method according to claim 1, characterized in that: In step S2, the inorganic bismuth salt is bismuth chloride.

6. The preparation method according to claim 1, characterized in that: In step S2, the reducing atmosphere is selected from a hydrogen / argon mixed gas.

7. The preparation method according to claim 1, characterized in that In step S2, the calcination temperature is 280-320° C., and the calcination time is 5-7 h.

8. The preparation method according to claim 1, characterized in that: In step S3, the etching time is 10-20 minutes.

9. A catalyst prepared according to the method according to any one of claims 1 to 8.

10. Use of the catalyst prepared according to the method according to any one of claims 1 to 8 in catalytic carbon dioxide oxidation to produce formic acid.

Citation Information

Patent Citations

  • Bismuth-palladium intermetallic compound electrocatalyst as well as preparation method and application thereof

    CN116905024A

  • Bismuth-doped palladium-carbon catalyst, and preparation method and application thereof

    CN118416886A